FORMAT AND CONTENT OF THE ACCOUNTING BALANCE SHEET IN THE MODERN ACCOUNTING AND ECONOMIC MODEL - LAGODIIENKO, NATALIA; IVANCHENKOVA, LARYSA; SKLIAR, LARYSA; IVANCHENKOV, VIACHESLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers the role and importance of the balance sheet in the system of economic valuations. By generalizing the existing balance theories and the development of the balance, the directions of its development are established and the main changes of its format for the future are outlined. This process is due to many factors and is mainly determined by the development of the information society and the growing information needs of stakeholders. The ability of the balance sheet to comprehensively assess the financial condition of the enterprise is possible by updating its structure. If the balance sheet formula remains unchanged for a long time, the components of the balance sheet elements (assets, capital and liabilities) undergo transformations due to the application of the new classification features. This has a direct impact on improving the quality of financial reporting of enterprises. It is substantiated that satisfying the information needs of stakeholders, the balance sheet format is improved under the influence of the adopted accounting system, the accounting model of the state and the accounting policy of the enterprise (organization). Taking into account the factors of influence on the balance of the enterprise specified in the article, it is possible to achieve its compliance with the modern accounting and economic model.Despite the legal minimum requirements for assets, capital and liabilities, the management of the balance sheet process is influenced by the company's accounting policies. Due to the criterion of materiality, companies can detail individual articles, or leave them in aggregate form, which allows to ensure either maximum transparency of the financial condition, or protection of economic data of the company. The inclusion of the book value of assets in the quantitative criteria for the classification of enterprises by size requires periodic review of ranges, expressed in conventional units, to ensure the principle of proportionality of the classification of economic entities. As the format and content of balance sheets of different economic entities differ in institutional sectors, as well as the size of enterprises, in order to ensure the unity of their generalized data and macroeconomic reports there is a need to develop and approve a single methodological approach to balance sheet, which would provide unambiguous uniformity of rules for all subjects of economic activity.
Keywords: balance sheet generalization; balance sheet; statement of financial position; balance sheet currency; balance sheet structure; balance sheet equation; analytical content of the balance sheet